Bioelectrochemical methanation by utilization of steel mill off-gas in a two-chamber microbial electrolysis cell - Spiess, Sabine; Sasiain Conde, Amaia; Kucera, Jiri; Novak, David; Thallner, Sophie; Kieberger, Nina; Guebitz, Georg M.; Haberbauer, Marianne (Frontiers in Bioengineering and Biotechnology, 2022)
Carbon capture and utilization has been proposed as one strategy to combat global warming. Microbial electrolysis cells (MECs) combine the biological conversion of carbon dioxide (CO2) with the formation of valuable products such as methane. This study was motivated by the surprising gap in current knowledge about the utilization of real exhaust gas as a CO2 source for methane production in a fully biocatalyzed MEC. Therefore, two steel mill off-gases differing in composition were tested in a two-chamber MEC, consisting of an organic substrate-oxidizing bioanode and a methane-producing biocathode, by applying a constant anode potential. The methane production rate in the MEC decreased immediately when steel mill off-gas was tested, which likely inhibited anaerobic methanogens in the presence of oxygen. However, methanogenesis was still ongoing even though at lower methane production rates than with pure CO2. Subsequently, pure CO2 was studied for methanation, and the cathodic biofilm successfully recovered from inhibition, reaching a methane production rate of 10.8 L m-2 d-1. Metagenomic analysis revealed Geobacter as the dominant genus forming the anodic organic substrate-oxidizing biofilms, whereas Methanobacterium was most abundant at the cathodic methane-producing biofilms.